ALTRUISME DAN SELF ESTEEM PENGARUHNYA TERHADAP MOTIVASI MENJADI RELAWAN MELALUI LOCUS OF CONTROL - Irawati, Rina (Program Studi Manajemen Institut Teknologi dan Bisnis Asia Malang, 2023)
A volunteer is someone who joins hands with groups, communities and institutions to produce a beneficial impact on the general public. There are several factors that can influence a person's motivation to be a volunteer. The purpose of this research was to examine the direct and indirect effects of altruism and self-esteem to volunteer motivation through locus of control. The method of analysis uses path analysis. The research sample was 76 volunteers at Rumah Makan Rakyat Malang. All items were declared valid and reliable. The results of the path analysis prove that there is a direct effect between altruism and self-esteem on motivation to volunteer with a significance <0.05. However, there is no direct effect between locus of control on motivation to volunteer because the significance value is > 0.05. It means that locus of control did not mediate altruism and locus of control on volunteer motivation. The biggest direct effect on motivation is self-esteem with the largest standardized beta value of 0.554.